Cognitive Behavior Therapy: Application of Intervention for Anorexia Nervosa - Santoso, Christine (ANIMA Indonesian Psychological Journal, 2010)
Cognitive behavior therapy helps anorexia nervosa clients reduce their disorder by cognitive restructuring and learning new adaptive eating behavior. The aim of this study was to examine the effect of cognitive behavior therapy on anorexia sufferers. Single case experimental design was applied in this research with three anorexia nervosa sufferers as subjects. A scale that was adapted from The Eating Attitude Test (EAT), self monitoring, observation and interview was used to collect the data. Results reveal that cognitive behavior therapy affect the tendency of anorexia nervosa in female adolescents. The result of the study are discussed. Terapi kognitif perilaku dapat membantu penderita anorexia nervosa mengatasi gangguan dengan restrukturisasi kognitif dan mempelajari perilaku yang lebih adaptif terkait dengan perilaku makan. Penelitian ini menguji pengaruh terapi kognitif perilaku terhadap penurunan kecenderungan anorexia nervosa pada remaja. Desain penelitian yang digunakan adalah desain eksperimen kasus tunggal dengan tiga subjek. Data diperoleh melalui skala adaptasi dari The Eating Attitude Test (EAT), pemantauan diri sendiri, observasi, dan wawancara. Hasil analisis menunjukkan ada pengaruh terapi kognitif perilaku terhadap kecenderungan anorexia nervosa pada remaja perempuan. Hasil penelitian didiskusikan lebih lanjut.